2018
DOI: 10.3390/met8010076
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Flow, Temperature, and Concentration Distribution Features of Combined Gas and Bottom-Electromagnetic Stirring in a Ladle

Abstract: Abstract:A novel method of combined argon gas stirring and bottom-rotating electromagnetic stirring in a ladle refining process is presented in this report. A three-dimensional numerical model was adopted to investigate its effect on improving flow field, eliminating temperature stratification, and homogenizing concentration distribution. The results show that the electromagnetic force has a tendency to spiral by spinning clockwise on the horizontal section and straight up along the vertical section, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The analysis of the harmonic electromagnetic field including the distribution of Lorentz force, magnetic flux density, and induced current density is obtained by solving the Maxwell equations and constitutive equations [25], and they can be rewritten as follows:…”
Section: Electromagnetic Modelmentioning
confidence: 99%
“…The analysis of the harmonic electromagnetic field including the distribution of Lorentz force, magnetic flux density, and induced current density is obtained by solving the Maxwell equations and constitutive equations [25], and they can be rewritten as follows:…”
Section: Electromagnetic Modelmentioning
confidence: 99%
“…The argon flow rates in the water model were calculated according to Equation (9), which were about 100-160 L/h. Since the flow rate of water is equal to the flow rate of liquid steel, the water flow was calculated according to Equation (10). In order to analyze the effects of the argon flow rate and casting speed on the argon bubble behavior in the nozzle, the experimental scheme is shown in Table 1.…”
Section: Experimental Schemementioning
confidence: 99%
“…Extensive studies [6][7][8] focusing on this technology have been conducted. The effect of argon gas on the flow of molten steel and slag entrapment in mold was revealed during the continuous casting process [9][10][11]. The theoretical results of Thomas [12] indicated that the argon bubbles in the nozzle during argon blowing could change the flow of the upper recirculation zone…”
Section: Introductionmentioning
confidence: 99%
“…Also, Sand et al [6] discovered that the combined method of side-traveling electromagnetic stirring (EMS) and argon blowing stirring is useful for reducing the fluctuation and deformation of free surface. Moreover, Li et al [7] reported that the combined method of bottom-rotating EMS and argon blowing stirring promotes the scatter of bubbles and reduces the impingement of bubbles on the slag layer in the process of ladle refining. These above-mentioned methods mainly adopted static magnetic field or low-frequency magnetic field.…”
Section: Introductionmentioning
confidence: 99%